Individualna doživljanja žensk z motnjami hranjenja - Pandel Mikuš, Ruža (Obzornik zdravstvene nege, 2003)
The article deals with individual experience of women with eating disorders. The author presents the results of qualitative analysis of nine interviews conducted with young women undergoing treatment at the Clinic for eating disorders. The final interpretation of the results obtained throughpractical experience is followed by a formulation of a workable theory, its integration into a broader theory on the subject, and the methodological self-reflection. In conclusion, several possible solutions of this personal and social issue are being proposed.
Keywords: Eating Disorders; Hranjenje, motnje; motnje hranjenja; Prevention And Control; psihologija; Psychology; Therapy; woman; ženske